Objek Materia Pemerintah Daerah Ditinjau Dengan Model Efetivitas Sistem Terbuka - Hamdun Hibatuloh; Randi Dwi Cahya Fitriyadi; Arkan A; Elang Danar Putra Anggriawan; Thoriq Hamimi Setiawan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Local governments have various material objects, such as natural resources, infrastructure, education, health, and so on. In a review of the philosophy of public administration with an open system model, regional government material objects must be managed in a transparent and accountable manner. What the government focuses on are principles transparency and accountability in the management of regional government material objects. It is so it is important to ensure that the management of such materia objects is carried out in a manner that honest, open and responsible. In managing regional government material objects, the community must be actively involved and given the opportunity to express their opinions.